Disparitas Pembangunan Ekonomi Antar Provinsi Di Pulau Sumatera Tahun 2012 -2016 - Muhammad Rusdi; Barika Barika; Izharudin Izharudin; Lela Rospida (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2019)
This study aims to find out how the level of regional inequality between provinces on the island of Sumatra and how the population, investment, government spending and inflation influence regional inequality in Sumatra. We also analyze the pattern of economic growth in Sumatra according to the class typology. We also estimate Regional Inequality (Region) by Williamson index and use multiple regression to analysis the determinant inequality. The results study shows that 60 percent of the provinces in Sumatra fall into the category of low inequality, these provinces are North Sumatra, West Sumatra, South Sumatra, Bengkulu, Lampung and the Bangka Belitung Islands. The province of Aceh is included in the category of moderate inequality. The other 3 provinces, namely Riau, Jambi and Riau Islands have High inequality indices. Overall, population growth, Investment, Capital Expenditures and Inflation variables together / overall have a significant influence on regional economic inequality variables. Partially variable population growth and capital expenditure have a significant positive effect, while the investment variable has a significant negative effect on the economic inequality of the Sumatra region. The variable inflation is not significant to the economic inequality of the Sumatra region. Based on the results of Klassen's typology analysis, it can be seen that the provinces of North Sumatra, West Sumatra, Jambi, South Sumatra, Bengkulu and Lampung are fast growing provinces (high growth but low income). Provinces that are included in the fast growth and high income class are the provinces of Aceh and Bangka Belitung and the category of relatively low and low income cities is the Riau Islands province.